INFLUENCE OF BUDDHISM ON THE EXPANSION OF WRITING IN THE MID SIXTH CENTURY YAMATO - D. A. Surowen (Вестник Кемеровского государственного университета, 2018)
The article features the influence of Buddhism, which appeared in Japan in the first half of the VI century, on the expansion of writing and written culture in Yamato. The author believes that the Chinese dynastic stories underestimated the expansion of writing in Japan during the VI century in their wish to link the appearance of the written language with Buddhism, which contradicts the finds of ancient Japanese epigraphic inscriptions on swords and mirrors made in the V century. The confusion in the Chinese sources probably arose from the ancient tradition of talking knots and cuts on wooden plates in the early VI century. Yamato had to refuse from this practice when Buddhism entered Japan in the early VI century. First, Buddhism was introduced at the court of the unrecognized Yamato ruler, prince Hironiwa (future Kimmei) in 538 A.D. It was officially recognized during his rule in 552 A.D., which was confirmed by the Chinese dynastic histories. To read Buddhist literature and write in good Chinese, new Japanese adepts and scientists had to master thieroglyphic writing.